Socio-economic status of fisherf(Jlk in relation to fish and fisheries of Hemavathy reservoir - Madhyastha, M N; Murugan, S (Indian Journal of Fisheries, 2011)
The Hemavathy reservoir has been constructed across the River Hemavathy at Gorur, Hassan district. The rivers Hemavathy and Yagachi which originate from Ballarayana Durga and Bababudangiri hills of Western Ghat, respectively, form the source of the reservoir. The reservoir has a waterspread area of about 2810 km2, and is situated at 12"04’0" Nand 76Â° 03’0" E at an elevation of 891 m MSL. The storage capacity is 37.10 TMC ft which can be used to irrigate approximately 0.28 million ha of land. In addition to irrigation, the water is used for drinking and other domestic purposes. Extensive fishery activities practised this Reservoir have made a major source of livelihood for the fishermen in its vicinity. Hence, the study was undertaken to understand and present suggestions to upgrade the status of the fishermen